A Fight for Gender Equality within the United States’ Government - Ni Made Citra Kusuma Dewi (Universitas Airlangga, 2018)
Due to the stereotypes that women are unable to do jobs besides household chores, the people mostly assume that women are unable to work in politics and government as well as men do. This assumption, implicitly, violates human’s right to reach their social welfare. This paper, hence, aims to explore how women are perceived and treated in the government of the United States, specifically in the Congress by analyzing the current situation through literature reading. Based on the historical studies, the authors argue that gender equality has not been applied properly in the United States’ political system. This case eventually results in the emergence of various doubts on the United States as a role model for countries around the world that promote her civilian rights as the main priority.